Positioning Animal Welfare in the One Health Concept through Evaluation of an Animal Welfare Center in Skopje, Macedonia - Radeski, Miroslav; O’Shea, Helen; De Meneghi, Daniele; Ilieski, Vlatko (Frontiers in Veterinary Science, 2018)
The Animal Welfare Center (AWC) in Macedonia was established in 2009. The objectives of the center are: animal welfare (AW) education, research, raising public awareness of AW and increasing cooperation between the stakeholders. One Health (OH) was not the major focus of the AWC work initially, but, rather, a focus that evolved recently. The objective of this study was to evaluate the AWC from the OH perspective as an example case for positioning the AW within the overall OH concept. Three types of evaluation were performed: 1) Assessment of OH-ness, by quantitative measurement of the operational and infrastructural aspects of the AWC; 2) Impact evaluation, by conducting quantitative surveys on stakeholders and students; and 3) Transdisciplinary evaluation, using semi-quantitative evaluation of the links of cooperation between the AWC and the stakeholders in society by the custom designed CACA (Cooperation, Activities, Communication and Agreement) scoring system. Results for the OH-ness of the AWC showed relatively high scores for OH thinking, planning and working and middle scores for OH learning and sharing dimensions, i.e. dominance of the operational over infrastructural aspects of the AWC. The impact evaluation of the AWC shows that familiarity with the OH concept among stakeholders was low (44% of the respondents). However, there was a commonality among stakeholder’s interest about Animal Welfare and OH. According to the stakeholders’ and students’ opinions, the influence of AW on Animal, Environmental and Human Health is relatively high (in the upper third of the 1 – 10 scale). The transdisciplinary evaluation of the AWC indicated the presence of transdisciplinarity work by the AWC, with a higher focus on the Universities and Research Institutions and some governmental institutions, and less linked with the NGO’s and Professional Associations (Chambers), e.g. the Veterinary Chamber in Macedonia. The evaluations conducted indicated that the AWC’s work is closely dedicated to improving animal, environmental and human health and has a considerable OH role among the stakeholders in the society. This study describes the significant role and importance that AW has in OH.